2000
DOI: 10.1097/00007890-200005270-00027
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Erectile Dysfunction After Renal Transplantation

Abstract: IIEF proved to be a valuable means of unveiling highly prevalent erectile dysfunction in male kidney transplant recipients. The negative impact of the time on dialysis was emphasized in the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
4
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 13 publications
9
53
4
4
Order By: Relevance
“…These findings are in line with those reported by others. 2 In this study, no statistically significant relationship between the haemodynamic parameters and cyclosporin A blood level could be demonstrated. These findings are supported by Ragazzi et al 17 who 18 Also cyclosporin A induces hypertension.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…These findings are in line with those reported by others. 2 In this study, no statistically significant relationship between the haemodynamic parameters and cyclosporin A blood level could be demonstrated. These findings are supported by Ragazzi et al 17 who 18 Also cyclosporin A induces hypertension.…”
Section: Discussioncontrasting
confidence: 58%
“…1,2 The etiology of erectile dysfunction in transplant recipients is often multifactorial. Vascular insufficiency as a cause of impotence in renal transplant recipients (RTR) has received limited attention.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue and psychosocial factors related to the presence of a chronic disease are also contributory factors. 7 In a cross-sectional study in 323 kidney transplant patients, 8 authors found that factors significantly and negatively related to ED were: age, time on dialysis, and iterative transplants. There is not a lot of information about ED of renal transplant bearers, but among the risk factors are underlying vascular factors, hypogonadism associated with immunosuppressive doses of steroids, and neurogenic factors associated with the main diagnosis (eg diabetes).…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have suggested that erectile function significantly improves after successful renal transplantation, [5][6][7][8] especially when the surgery is performed at a younger age, 5 other studies have shown minimal effects of transplantation on erectile performance or even deterioration. [9][10][11][12] The overall prevalence of ED after KT remains high, ranging from 48.9% 13 to 55.7%. 11 The potential causative effects of ED in transplant recipients may include anxiety, medication side effects, impaired penile vascularity and failure to resolve hormonal abnormalities or underlying disease comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] The overall prevalence of ED after KT remains high, ranging from 48.9% 13 to 55.7%. 11 The potential causative effects of ED in transplant recipients may include anxiety, medication side effects, impaired penile vascularity and failure to resolve hormonal abnormalities or underlying disease comorbidities. 14 Reduced cavernosal arterial inflow was hypothesized as the likely cause of ED in a series in which the internal iliac artery was employed for end-to-end anastomosis.…”
Section: Introductionmentioning
confidence: 99%